Kajian Angkutan Sedimen Dasar Pendekatan Laju Angkutan Sedimen Tak Berdimensi Einstein (1950) - Junaidi, Junaidi (Politeknik Negeri Semarang, 2012)
Rivers are the best sites to observe the natural effects of sediment transport. Phenomenon of sediment transport in the flow was much scrutinized by experts and some sediment transport equations have been developed. But the performance of these equations is still controversial. Gomez and Church (1989) evaluated a number of sediment transport equations were developed for flows with a gravel base and find that none who have a good consistent performance. This paper examined the sediment transport with a case study on Krasak river in Yogyakarta. This paper intended to test the accuracy of the count by using a dimensionless sediment transport equations of Einstein (1950) on sediment transport measurements. Based on the relationship between the flow parameters (?) and the transport parameter (?) of this study compared to the graph of Einstein (1950), it appeared that some of the research data plot was fairly spread. In the plot of data with ? = 2.00 to 4.00, the trend of the data deviated far enough above the curve of Einstein. In the plot of data with ? = 1.35 to 2.00 and ? = 4.00 to 5.00; trends in the data were slightly above the curve of Einstein. While the data with ? = 1.06 to 1.35 trends to follow the curve of Einstein. This last data has a coefficient ? closed to uniform.